The Effect of Endoscopic Endonasal Transsphenoidal Skull Base Surgery on Cochlear Function - Ates, Murat Samet; Benzer, Murat; Kaya, Isa; Biceroglu, Huseyin; Ozgiray, Erkin; Midilli, Rasit; Karci, Halil Bulent; Gode, Sercan (Journal of Neurological Surgery Part B: Skull Base, 2019)
Endoscopic transsphenoidal skull base surgery (ETSS) has become a standard approach in the treatment of sellar and clival lesions, such as pituitary adenoma and chordoma. Due to the close proximity of the clivus and the sella turcica to the inner ear, it is thought that bone drilling in the surgery may have effects on hearing. The aim of this study was to assess the effect of bone drilling in ETSS procedure on cochlear function. This study was performed on 18 patients who underwent ETSS procedure between December 2016 and May 2017. The study was designed as a prospective study. All of the data were prospectively collected. These included demographic data, date of surgery, type of surgery, preoperative pure-tone audiometry, and preoperative and postoperative distortion product otoacoustic emission (DPOAE) measurements. Of the DPOAE measurements of the patients who were operated for pituitary adenoma, there was a statistically significant difference between the signal-to-noise ratio (SNR) measurements at 0.5, 1, 2 and 4 kHz (p < 0.05). Additionally, there were no significant differences in preoperative and postoperative SNR measurements of six patients who were selected for clivus chordoma. When the preoperative and postoperative tonal audiometric tests of the patients were compared, no statistically significant difference was found (p > 0.05). In conclusion, it is found that bone drilling in ETSS procedure has a negative effect on cochlear function in the early period. This is the first study to evaluate the degree of noise-induced cochlear damage in patients who were gone under ETSS procedure.
Keywords: pituitary; clivus; endoscopic; chordoma; cochlear function